MENGANALISIS FAKTOR YANG MEMPENGARUHI PERMINTAAN KREDIT PEMILIKAN RUMAH - Prasetyo, Achmad Budi; Pudjihardjo, M (Journal of Development Economic and Social Studies, 2024)
The increasing need for housing encourages people take other alternatives, such as using Home Ownership Loans (KPR) as an alternative in obtaining housing. There are some factors that influence the community as consumers in taking / using mortgages, some factors include customer income, house prices, interest rates, down payments, loan terms, and the simultaneous influence of all factors.  This study aims to provide an overview of the factors that influence the demand for mortgage loans in Watubangga urban village housing in Kendari city.   The method used in this research uses descriptive quantitative, where this approach explains the phenomenon of the situation, measures the relationship and draws conclusions based on the use of numbers.  The findings of this study are partial factors that affect mortgage credit such as customer income, price of a house and time period are positively significant, which means that the increase in these partial factors increases the community's intention to take out a mortgage. However, it is inversely proportional to partial factors such as interest rates and down payments. Even so, the effect of these factors is simultaneously positively significant.